Study of Nature and Gender differences of a group of Persons Suffering from Tinnitus - Sujoy Kumar Makar; Rajeev Jalvi; Ashok Kumar Sinha (Journal of All India Institute of Speech and Hearing)
Tinnitus is widespread amongst clients attending hearing clinics and has been associated with a range of physical and emotional disorders (Hallam R.S., Jakes, S.C., and Hinchcliffe, R.. 1988).Hence to understand the distress caused by tinnitus and its relationship with the nature of tinnitus so as to suggest the appropriate treatment, there is the need to study the audiological and psychological characteristics of a group of tinnitus sufferers on the basis of verbal description of tinnitus and audiological measurements of tinnitus to understand nature and gender differences. Fifty adults in the age range of 18 to 60 years with subjective tinnitus with bilateral normal hearing or pure SNHL ranging from mild to moderately severe were selected. An audiological profile of each subject was prepared on the basis of brief case history of subject, otoscopic examination, pure tone audiometry, impedance audiometry, effective masking level, was conducted for all cases. A psychological profile was developed by using Tinnitus Reaction Questionnaire (TRQ) and Nature of Tinnitus Questionnaire (NTQ). These questionnaires were translated and adopted in Hindi and Bengali language after appropriate standardization procedure. 60% reported that they do not have any idea regarding probable cause of their tinnitus. Not even a single subject in the present study reported the cause of their tinnitus as consumption of alcohol. 74% subjects of this study reported that there is no fluctuation in the pitch of their tinnitus. However, 68% reported loudness of tinnitus is fluctuating. There was a significant correlation between the impact of tinnitus and disturbance of sleep caused by it with increase in depression and anger (.483). However, no significant co-relation was seen between distressed caused by tinnitus and duration of tinnitus (-.034). The multiple nature/sounds of tinnitus had far more devastating effects or serious impact on ’tinnitus sufferers’ than the single sound/nature. Gender differences were also found among tinnitus sufferers while assessing the audiological and psychological measures of tinnitus. Female subjects also reported a higher level of emotional reaction with a mean of 35.9 to their tinnitus as compared to males with a mean of 31.7. Tinnitus has resulted in multifold effects/impacts on tinnitus sufferers where it has made them feel unhappy, tense, irritable, depressed, annoyed, distressed and frustrated. It has interfered with their enjoyment, their relaxation, their sleep, and forced them to avoid quite and social situations. These studies would further help in the overall management of the patient suffering from tinnitus.